O Impacto da telessaúde em cuidadores de usuários de um Serviço de Atenção Domiciliar - Vargas, Lorena Silva (2022)
Introduction: Home care is an alternative to institutionalization of hospitalized people, as well as it can prevent unnecessary hospitalizations. In addition, it enables the possibility of offering support to Primary Care teams and families regarding the monitoring of those who need care provided at home. Despite the benefits of home care, there is still little scientific evidence that addresses the impact that a person cared at home generates for the family context, with telehealth being a possibility to minimize this challenge. In this context, due to the needs presented by the group of caregivers of users in long-term oxygen therapy (LTOT) of the Home Care (HC), whose demands are specific and, in general, need to be remedied immediately, the look turned to this public of caregivers. Objective: To identify the impact of telehealth on the aspects of physical and emotional health of caregivers of LTOT users active in HC. Method: This is a crossover randomized clinical trial with 32 caregivers, developed in a HC of a medium-sized municipality of Goiás State/Brazil, from May to December 2021. Each participant received the two proposed interventions: (A) experimental intervention that consisted of two-way communication, sending informative videos by the researcher and sending and receiving videos, audios and text messages related to the caregiver’s demands; and (B) intervention that consisted of unidirectional communication, by the researcher only sending informative videos. Participants were divided into two groups: Experimental Control Group (EC), composed of participants submitted to experimental followed by control intervention; and Control-Experimental Group (CE), composed of participants submitted to control followed by experimental intervention. After consent, each participant was randomly assigned to what was considered as EC Group or CE Group. In the experimental intervention, caregivers recorded messages in care situations that they considered complex or that aroused doubts in a freeway, using the WhatsApp Messenger® app, for secure smartphone contact exclusive to the study. Subsequently, the demands were shared with the interdisciplinary team, composed of HC professionals, for analysis and referrals. The two researchers responsible for the study intervention provided individualized guidance and feedback to the caregiver based on discussion with these HC professionals. Data were collected three times throughout the study with application of instruments: baseline (moment without interventions for initial data collection), washout (at the end of 8 weeks) and final (at the end of 16 weeks). In-person and/or remote home visits, conducted by a member of the research team, occurred to collect the signature of the Informed Consent Form and to collect data in the three moments. Data collection used a questionnaire with sociodemographic questions and the instruments Self Report Questionnaire 20 (SRQ-20); The World Health Organization Quality of Life (WHOQOL-BREF); Zarit Caregiver Burden Interview (ZBI) and Pittsburgh Sleep Quality Index (PSQI). To compare the moments over time, the Friedman test for the distribution-free data was used; and for the normal distribution data, the Analysis of Variance (ANOVA) for Repeated Measures was used. Within each moment comparing the EC Group with the CE Group, the Kruskal-Wallis Test for the distribution-free data was used; and for the normal distribution data, the ANOVA for Independent Groups. The result with p<0.05 was considered statistically significant. Results: The results showed that, about the order of application of the intervention for the dominance 3 (social relations) of the WHOQOL-BREF, there was statistical significance for those who participated in the EC group (p=0,03); and that in relation to the domain 4 (environment) of the same instrument differences between the EC and CE Groups after the two intervention schemes (p=0,04). Regarding the application of the PSQI instrument, although they did not identify a statistically significant impact, there was a reduction in mean scores between the EC and CE groups, which suggest an improvement in sleep quality. Final considerations: In short, this experiment showed that telehealth is a powerful tool to support caregivers of adults in LTOT, with a positive impact on the quality of life and sleep of these caregivers. Clinical trials with long-term post-intervention follow-up should be conducted to search for new findings.